Size reduction of vivaldi antenna array for microwave imaging - Abdulqadir Farah, Mohamed (2020)
UWB antennas with compact size, stable patterns of end-fire radiation and high gain find many of applications such as radar, microwave imaging, remote sensing. To achieve these goals, a compact-sized end-fire slot antenna (TSA) is a good candidate as it offers broad impedance bandwidth and stable radiation patterns, and high gain characteristics In this project, Vivaldi antenna array is designed, one antenna element is designed using FR-4 substrate which has relative permittivity of 4.3. and thickness of 1.6 mm. Furthermore, the single element is investigated to cover an ultra-wideband from 3.1 to 10.6 GHz by using Computer based Simulation Technology for Microwave studio (CST MWS) reducing the size of antenna will lead to gain reduction as well. Therefore, it is crucial to obtain a compact antenna with an acceptable return loss and radiation pattern. Hence, a single element antenna of size (36×42.8